Evaluation Of The Periodic Salary Increase Information System Program (Sigaber) In The Department Of Education And Culture Of Ntt Province, A Study From The Aspects Of Accountability, Transparency, And Effectiveness - Marsela Yulianti Nitbani; Melkisedek NBC Neolaka; Delila A. Nahak Seran; Rafi Akhsanul Kholikin (CV. AFDIFAL MAJU BERKAH, 2026)
The implementation of the Periodic Salary Increase Information System (SIGABER) at the East Nusa Tenggara Province Education and Culture Office still faces various obstacles in the aspects of accountability, transparency, and effectiveness that affect the quality of digital-based administrative services. This study aims to evaluate the implementation of the SIGABER Program based on the aspects of accountability, transparency, and effectiveness. The study used a descriptive qualitative approach. The study population was the parties involved in the implementation of SIGABER, while the sample was determined purposively by 10 informants consisting of the Head of the Personnel and General Affairs Subdivision, six SIGABER operators, and three ASN and teachers who use SIGABER. Data were collected through interviews, observations, and document studies with the researcher as the main instrument. Data analysis used the Miles and Huberman model through data reduction, data presentation, drawing conclusions, and tested with triangulation of sources, techniques, and time. The results of the study indicate that SIGABER has improved management accountability, transparency of service information, efficiency of administrative processes, and the quality of periodic salary increase services. However, obstacles were still found in the form of incomplete documents, internet network disruptions, data input errors, weak coordination, and changes in school operators without notification. This study concludes that the implementation of SIGABER has been running quite well in supporting digital-based personnel administration services, but still requires strengthening coordination, compliance with procedures, infrastructure improvements, and user assistance so that program implementation is more optimal.